Plasma and Saliva Irisin Levels of Patients with Diabetic Nephropathy and Non-Diabetic Proteinuria - Gurel, Ali; Atli, Hasan; Duzenci, Deccane; Aydin, Suleyman; Dogukan, Ayhan (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2015)
OBJECTIVE: Primary glomerular diseases or some systemic disorders such as diabetes (DM) may cause proteinuria. Irisin (IRI) is a hormone secreted as a response to physical exercise by the skeleton muscle and thought to be protective against many metabolic disorders such as DM, obesity. Decreased levels of irisin were observed in chronic kidney disease (CKD), type 2 DM and obesity. The aim of this study was to determine IRI levels in blood and saliva of proteinuric patients with and without diabetes. MATERIAL and METHODS: Sampling was from 15 diabetic, 15 non-diabetic proteinuria and 13 healthy control subjects. IRI concentrations were measured by using commercial ELISA kits. Statistical analysis was performed using SPSS 12. Groups were compared by the Kruskal-Wallis test and then Mann-Whitney post hoc test was performed. RESULTS: Plasma and saliva IRI levels of non-diabetic group were higher than the diabetic group. There was a significant positive correlation between plasma IRI concentrations and HDL, albumin levels but a negative correlation between plasma IRI and LDL levels. CONCLUSION: IRI levels were low both in plasma and saliva in diabetic subjects. IRI may be an important marker and/or therapeutic agent for disorders associated with energy expenditure and kidney diseases in the future.
Keywords: Proteinuria; Diabetic nephropathy; Irisin